2018
DOI: 10.1007/s13770-018-0135-9
|View full text |Cite
|
Sign up to set email alerts
|

Collagen Scaffolds in Cartilage Tissue Engineering and Relevant Approaches for Future Development

Abstract: BACKGROUND: Cartilage tissue engineering (CTE) aims to obtain a structure mimicking native cartilage tissue through the combination of relevant cells, three-dimensional scaffolds, and extraneous signals. Implantation of 'matured' constructs is thus expected to provide solution for treating large injury of articular cartilage. Type I collagen is widely used as scaffolds for CTE products undergoing clinical trial, owing to its ubiquitous biocompatibility and vast clinical approval. However, the long-term perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
133
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(143 citation statements)
references
References 190 publications
(413 reference statements)
4
133
1
5
Order By: Relevance
“…Pore size of the top layer was 332.71 ± 52.63 μm. This was consistent with the existing study, which reported that pore sizes larger than 300 μm were advantageous to support the chondrogenic differentiation of rBMSC and their subsequent production of cartilage‐related matrices . Pore size was decreased gradually from the top layer to the bottom.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Pore size of the top layer was 332.71 ± 52.63 μm. This was consistent with the existing study, which reported that pore sizes larger than 300 μm were advantageous to support the chondrogenic differentiation of rBMSC and their subsequent production of cartilage‐related matrices . Pore size was decreased gradually from the top layer to the bottom.…”
Section: Discussionsupporting
confidence: 92%
“…This was consistent with the existing study, which reported that pore sizes larger than 300 μm were advantageous to support the chondrogenic differentiation of rBMSC and their subsequent production of cartilage-related matrices. 34 Pore size was decreased gradually from the top layer to the bottom. The contents of CS and SF changed in different layers of the scaffold, mimicking the histological structure of joint cartilage.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies reported that the pivot role, for hASCs osteogenic differentiation, is played by the HA, whereas the collagen mainly supports the survival, proliferation, and chondrogenic differentiation …”
Section: Discussionmentioning
confidence: 99%
“…Cartilage tissue engineering is considered a promising modality for effective repair of damaged cartilage tissue 7,8 . The procedure most often used in cartilage tissue engineering involves a suitable combination of seeded cells, a biocompatible scaffold, and biological factors that support cartilage formation.…”
Section: Introductionmentioning
confidence: 99%